Icarus and sports after COVID 19: Too close to the sun? - Baggish, A L. B.; Levine, B. D. (Circulation, 2020)
The resumption of organized athletics at every level will involve some form of medicalclearance. We propose that all screening efforts should define and manage the cardiac footprints of COVID-19 infection.